The Effect of Maternal Body Mass Index on in Vitro Fertilization-Intracytoplasmic Sperm Injection Treatment: A Prospective Comparative Study - Ozturk Inal, Zeynep; Inal, Hasan Ali (Gynecology Obstetrics & Reproductive Medicine, 2022)
Objective: To evaluate whether or not maternal body mass index affects pregnancy rates following in vitro fertilization-intracytoplasmic sperm injection treatment. Study Design: A total of 869 patients who had undergone in vitro fertilization-intracytoplasmic sperm injection treatment between 2012 and 2017 were included in this study. The participants were stratified according to maternal body mass index as Group 1 (body mass index <25 kg/m2; n=394), Group 2 (25 kg/m2< body mass index <30 kg/m2; n=303), and Group 3 (body mass index >30 kg/m2; n=172). Results: While there were no differences between the groups in terms of age, smoking status, etiology of infertility, thyroid-stimulating hormone, prolactin levels, antral follicle count, and stimulation protocol (p>0.05), there was a significant statistical difference in terms of body mass index, duration of infertility, baseline follicle-stimulating hormone, luteinizing hormone, estradiol (E2), duration of stimulation, total gonadotropin dose required, peak E2 levels, progesterone levels, endometrial thickness on hCG administration, and cycle cancellation rate (p<0.05). In addition, the numbers of oocytes retrieved (groups 1 vs 3, p=0.011), metaphase II (groups 1 vs 3, p=0.017) and 2 pronucleus (groups 1 vs 3, p=0.010 and groups 2 vs 3, p=0.010), and the rates of clinical pregnancy (40.1% vs 33.2% vs 23.8%, respectively), live births (33.6% vs 23.7% vs 13.9%, respectively), and miscarriages (17.7% vs 28.6% vs 44.7%, respectively) were also different between the groups (p<0.05). Conclusion: Our data suggest that there is an inverse impact of increased body mass index on laboratory and reproductive outcome parameters of in vitro fertilization-intracytoplasmic sperm injection treatment. Taking cost-effectiveness into consideration, weight loss should be suggested before ovulation is induced.